Pengaruh Sales Growth, Kualitas Audit dan Opini Audit Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Pemoderasi - Nurhasanah, Ismi; Napisah, Napisah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
This research aims to analyze the factors that influence company value. The factors studied are sales growth, audit quality and audit opinion with company size as a moderating variable. The research population is non-cyclical sector companies on the Indonesia Stock Exchange in 2018 - 2022. Sampling used a purposive sampling method, namely 220 data. The research uses multiple linear regression analysis techniques. The research results show that sales growth, audit quality and audit opinion simultaneously influence company value. Audit opinion partially influences company value, while sales growth and audit quality have no effect. Company size can only moderate the relationship between audit opinion and company value, while sales growth and audit quality cannot.